الآراء الأصولية للإمام ابن الفرس الغرناطي من خلال كتابه أحكام القرآن - سورة البقرة أنموذجا - الأقرع, آسية (University of Eloued-جامعة الوادي, 2015)
Article fundamentalism is considered a tool to derive rulings from the original sources. And the source of her first book of Allah, the Almighty. And interpretation facilitate access to it. So he wrote a book Granada son Persians in this art and summarized the provisions of the Koran. It is the best of what has been written in this area. To give a glimpse, even simple about this book and its author and the statement of some of its features. Began in the study of this subject, entitled: fundamentalist views to the son of the Persians Granada through the book of the Koran - Surat Al-Bakara model – I devided this subject into two chapters, the first one is specialized to identify the writer and the book, and I devided this chapter too into two themes: The first, I speak about the writer; his personal life; his teachers and students and his scientific position. In addition, I speak about his doctrine and belief; his important books and novels. This was in five claims. The second, I defined the book which we study and I devided this theme into four claims: in the first I speak about the book and its relation with the writer. The second is specilized to the sources of the book, but in the third I distiguished the method of Ibn lfaras in his book. In th fourth one I mentioned some of his scientific choices. For the second chapter from this research i devided it into two themes and every single theme contains four claims: in the first theme I inserted some questions in the section of judgements which is as follows: the first claim in the judgements of high-position persons before the religion comes. In the second adressing the unbelievers about the branches of the Islamic Sharia. In the third one has the Prophet another religion from another prophet before his sending. But the fourth one is about gathering. And these questions was studied according to three branches which are liberating the controversy spot and mentioning the scientists sayings and their evidences, then ifinished these questions by clarifying the opnion of Ibn Alfaras Algarnati. In the second theme I inserted questions in words' significances and it was in four claims too which are as follows: invalidation or abolishing, specializing, order and forbidding. Finally, I closed the subject with some results which we reached through this research and some important recommendations.
مذكرة ماستر
Keywords: الآراء الأصولية/ابن الفرس الغرناطي/أحكام القرآن/سورة البقرة; Fundamentalist views/Ibn al-Furs al-Gharnati/Provisions of the Qur’an/Surat Al-Baqarah